Distribution of Polycyclic Aromatic Hydrocarbons (PAHs) in sludge organic matter pools as a driving force of their fate during anaerobic digestion. (February 2016) - Aemig, Quentin; Chéron, Claire; Delgenès, Nadine; Jimenez, Julie; Houot, Sabine; Steyer, Jean-Philippe; Patureau, Dominique
Highlights: PAHs distributed in all organic matter pools (OMP). Poor dissipation of native PAHs mostly associated to low accessible OMP. Larger dissipation of spiked PAHs initially present in accessible OMP. Transfer of part of spiked PAHs to non-extractable OMP. PAHs behavior driven by PAHs properties and quality/quantity of associated OMP. Abstract: The fate of organic matter during anaerobic digestion of sewage sludge was studied in batch systems thanks to a sequential chemical fractionation of the particulate phase coupled to fluorescence spectroscopy. Polycyclic Aromatic Hydrocarbons (PAHs) distribution within the organic pools was characterized from their analysis in the residual fraction after each extraction. Both methods were combined to understand the link between PAHs presence in organic pools and their spectral characterization after extraction. Two batch systems (sludge and inoculum mixture) were set up to study the impact of PAHs spiking on their fate and distribution. The sequential fractionation allowed us to extract and characterize about 50% of total Chemical Oxygen Demand. Moreover, fluorescence spectroscopy helped us to understand the organic pools evolution: the most easily extracted pools composed of protein-like molecules were highly degraded meaning that chemical accessibility mimics the bioaccessibility to degrading microorganisms. PAHs were present in all pools of organic matter but native PAHs were mainly present in low accessible (hardly extractable) fractions and during anaerobic digestion, they accumulated in the non-accessible (non extractable) fraction. Spiked PAHs were more dissipated during anaerobic digestion since spiking made them present in more accessible fractions. During the anaerobic digestion, contrary to native PAHs, spiked ones relocated toward less accessible organic fractions confirming the ageing phenomenon. PCA analysis showed that, in spiked mixture, PAHs presence in organic pools is linked to both PAHs physical–chemical properties and quality/quantity of the associated organic pools.